THU0241 Presence of Germinal Centers in Diagnostic Biopsies of Primary Sjögren's Syndrome Patients Is Not A Risk Factor for The Development of Parotid Malt Lymphomas. (15th July 2016) - Haacke, E.A.; Vissink, A.; van der Vegt, B.; Spijkervet, F.K.; Bootsma, H.; Kroese, F.G.
Abstract : Background: B cell hyperactivity is a hallmark of primary Sjögren's syndrome (pSS) and plays a critical role in sustainment and progression of pSS. 1 Hyperactivity is reflected by the presence of germinal centers (GCs) in periductal lymphoid infiltrates in the salivary glands. Risselada et al 2 reviewed the presence of GCs in the salivary gland biopsies of pSS patients. On hematoxylin and eosin (HE) stained sections a mean weighted percentage of 25.1±5.0% (range 18.3–33%) of GCs positivity was present. On CD21 sections, staining follicular dendritic networks, this increased to 35.3±14.8% (range 19–58.8%). A serious complication of pSS is the 5–10% lifetime risk of developing non-Hodgkin B cell lymphomas. 3 Most lymphomas associated with pSS are of the Mucosa Associated Lymphoid Tissue (MALT) type, which typically arise in parotid glands. Which pSS patients will develop non-Hodgkin's lymphomas is largely unknown, but several risk factors have been identified. Presence of GCs in minor salivary glands at diagnosis of pSS has been postulated as a risk factor. Theander et al 4 observed that six out of seven pSS patients that developed malignant lymphomas had GCs in their initial diagnostic minor salivary gland biopsy. However, a drawback of that study was that also lymphomas not characteristic for pSS such as follicular lymphoma and anaplastic T-cell lymphoma were included. 4 Objectives: The aim of this study was to explore the possible role of GCs as risk factor for malignant lymphoma development in pSS restricting ourselves to lymphomas which are typically associated with pSS, namely parotid gland MALT lymphomas. Methods: In a cohort of 56 pSS patients with parotid MALT lymphomas we were able to collect and reassess tissue sections from 14 salivary gland biopsies (11 minor, 3 parotid) taken at diagnosis of pSS, i.e. before diagnosis of MALT. Paraffin sections were analyzed for the presence of GCs on HE sections and, more sensitively, by B cell lymphoma 6 protein (BCL6) staining. Results: HE stained sections of 11 diagnostic minor salivary gland biopsies revealed that GCs were present in 2/11 (18%) biopsies (Fig. 1 a, c). BCL6 staining showed a small GC in one additional patient in the initial biopsy (Fig. 1 b, d). Thus, GCs were present in 3/11 labial salivary gland biopsies (27%). Including diagnostic parotid gland biopsies, GCs were present in 4/14 (29%) HE stained sections and in 5/14 (36%) BCL6 stained sections. The mean interval between diagnosis of pSS and parotid MALT lymphoma was 6.0 yr (range 0.2–14.4 yr). Conclusions: In this study percentages of GCs in salivary gland biopsies prior to MALT lymphoma were comparable to the percentage of GCs positive biopsies in the general pSS population. 2 We therefore conclude that presence of GCs in diagnostic (minor) salivary gland biopsies is not predictive for developing pSS associated parotid gland MALT lymphomas. References: Kroese FG, et al. Expert Rev Clin Immunol 2014 Apr;10(4):483–499. Risselada AP, et al. Semin Arthritis Rheum 2013 Feb;42(4):368–376. Voulgarelis M, et al. Arthritis Rheum 1999 Aug;42(8):1765–1772. Theander E, et al. Ann Rheum Dis 2011 Aug;70(8):1363–136. Disclosure of Interest: None declared